Strategi konseling gizi telenutrition dan kepuasan klien: studi kasus layanan oleh dietisien - Siti Intania; Elfrida Twinsani Eggelion Missi; Yosephin Anandati Pranoto (Jurnal Gizi Klinik Indonesia, 2026)
Telenutrition counseling strategies and client satisfaction: a case study of dietitian service Background: Digital technology has expanded telenutrition, improving accessibility, especially after the COVID-19 pandemic. However, its success depends on effective communication strategies that achieve high satisfaction and sustainable changes in client behavior.Objectives: This study aimed to identify the communication strategies used by the dietitian in telenutrition-based nutrition counseling and describe clients’ satisfaction with the service. Methods: This study used a mixed-methods design, combining qualitative and quantitative approaches. Qualitative data were collected through an in-depth interview with a dietitian, while quantitative data were collected using a 1-4 Likert-scale satisfaction questionnaire for 8 clients. Clients were selected using consecutive sampling. Data were analyzed narratively and descriptively. Results: The dietitian used Google Meet and Instagram as online media. Interpersonal communication techniques emphasizing clarity, empathy, openness, supportiveness, and responsiveness were applied. The counseling technique combined cognitive behavior therapy, solution-focused therapy, and motivational interviewing. Supportive media, such as a diet recommendations handout, food portion photos, visual illustrations, and a food diary, were also used in counseling. The satisfaction survey showed high satisfaction, with an average score of 3.88 out of 4 across accessibility and cost, communication quality, information clarity and relevance, impact and benefits, and general satisfaction. Conclusions: This case study demonstrates high client satisfaction with the dietitian's communication strategies for delivering telenutrition services.